Assessing the visual quality of rural villages in China, compared to urban residential areas. Issue 5 (2nd September 2016) - Zhao, Jingwei; Xing, Lu; Li, Rujia; Sun, Tong
Abstract : Traditional villages in China show a pattern of 'self-organization'. There is unplanned overall layout of space elements within the village landscape. Since the 'Building a New Countryside' policy, professionals have been active in design of the village landscape. The first step is to identify the distinguishing features of the traditional village landscape. This paper aims to identify the distinguishing features of village landscape compared with an urban residential area. The results indicate that abundant plants, shabby houses, monotonous colour, badly-maintained environment and closed space are the distinguishing features. A clean environment and high vegetation coverage are important.